Implementasi Kebijakan Pengamanan Barang Milik Daerah Di Pemerintah Kabupaten Buleleng - Shuarsini, Putu; Widnyani, Ida Ayu Putu Sri (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2025)
Regional Property Security (BMD) is part of regional financial management that supports the implementation of government and community services. To realize good governance, BMD security must be carried out optimally. However, the 2022 BPK Audit Results Report shows that BMD security in Buleleng Regency is still not optimal. This study aims to analyze the implementation of BMD security policies in Buleleng Regency. This study uses a qualitative descriptive method at BPKPD Buleleng Regency, with the researcher as the main instrument. Data was collected through observation, interviews, documentation, and online searches, with purposive sampling to determine informants. This study shows that the implementation of the Regional Property Security policy in Buleleng Regency has not been optimal, especially in administrative, legal, and physical security. The main obstacles include a lack of understanding of policies, limited human resources, and low competence in the use of the BMD SIPKD application. Improvement efforts include periodic socialization, technical guidance, and inventory of regional assets.